Use an Organic Biostimulant (Vermicompost Tea) For Enhancement In Vıtro Callus Growth in Sainfoin (Onobrychis viciifolia Scop.) - Ramazan Beyaz; Fevziye Şüheyda Hepşen Türkay (Turkish Journal of Agriculture: Food Science and Technology)
The health and vitality of callus growth is one of the prerequisites for the success of further in vitro studies. This study investigated the efficiency of different percentage (0%, 10%, 20%, 30%, and 40%) of vermicompost tea as an organic substance on in vitro callus growth in sainfoin. Morpho-physiological responses of calli to vermicompost tea measured under in vitro conditions. As a result of this investigation, a combination of plant growth regulators (4 mg/l BAP and 0.5 mg/l NAA) with 20% of vermicompost tea causing significant callus initiation and growth in sainfoin stem explants. Under the light of these scientific findings, vermicompost tea might be used as an organic bio stimulant for efficient callus growth and complementary to commercial chemical hormones in sainfoin. This research is important due to it can contribute positively to the plant species that are difficult in terms of callus growth and plant regeneration in tissue culture.